Optimizing geriatric health through early detection in a nursing home at South Tangerang City - Gunawan, Shirly; Amimah, Ranindita Maulya Ismah; Adnan, Naufal Ikbar Rian; Sinaga, Oktri Lentina; Maharani , Syifa Shabrina; Leonita , Stefani; Yosafat, Fernando; Arinanda , Septian; Pratiwi, Adelia Helmi; Syarifah , Anisa Ulaya (Universitas Muhammadiyah Malang, 2026)
Indonesia is entering an aging population phase, characterized by a significant rise in the number of elderly individuals. As they age, they are more prone to diverse health problems that require holistic care. Detecting health issues early is vital to prevent worsening conditions, reduce illness and disability, and improve the quality of life of the elderly. The activity focuses on empowering elderly residents and staff in nursing homes to identify health issues at an early stage. This community service activity applied a descriptive qualitative approach. By conducting interviews, observations, and examinations, the team identified the main complaints and health conditions experienced by most elderly residents in nursing homes. A total of 75 elderly residents underwent health screenings, including 60 females (80%) and 15 males (20%), with an average age of 78.92 years. The screenings covered medical record reviews, interviews, vital sign checks, and health education sessions. Hypertension, dyslipidemia, diabetes mellitus, hyperuricemia, and cataracts were identified as the five most common illnesses among elderly residents. The predominant complaints reported were muscle pain, headaches, skin injuries/bruises, and itchy skin. Through early detection, holistic assessment, and risk factor identification, elderly health can be optimally maintained, quality of life enhanced, and aging experienced with greater independence, comfort, and meaning.